Tindak Pidana Korupsi Perspektif Filsafat Iman Kristen - citranu citranu (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2020)
The Corruption is an act that is prohibited by human law and God's law. The essence of corruption is actions that are contrary to the truth of God's Word, the values ​​contained in corruption are sin or evil. The Methodology of corruption through misdirection, lies, fraud and other evil deeds. The Corruption according to the philosophy of the Christian faith aims to bring people to perish and destruction, The corruption is contrary to God's word and law. The prevention and eradication of corruption can only be done by strengthening the Christian faith, namely applying the law of love in human life.